TINJAUAN YURIDIS PERATURAN DAERAH NO. 02 TAHUN 2011 PENERAPAN SANKSI ADMINISTRASI DAN SANKSI PIDANA TERHADAP PEMBUANG SAMPAH - Fitri Nuur Handayani (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT This legal writing aims to determine the implementation of regulations on waste management. Trash is a residual activity of human and / or natural process in the form of solid. This problem is always inherent in everyday life.We can also know the existence of administrative sanctions and criminal sanctions in the Local Regulation No. 02 Year 2011 About Waste Management. Because the rule has been implemented, so the attitude to obey the rules and not to be violated in order for self-discipline.The role of the community is very important, in Local Regulation No. 02 Year 2011 About Waste Management. The government wants people to be aware and care about the environment, not to waste and take responsibility for their actions.Keywords: Waste, Administrative Sanctions and Criminal Sanctions.